2019
DOI: 10.1038/s41598-019-42641-9
|View full text |Cite
|
Sign up to set email alerts
|

Release of eDNA by different life history stages and during spawning activities of laboratory-reared Japanese eels for interpretation of oceanic survey data

Abstract: To assist in detection of offshore spawning activities of the Japanese eel Anguilla japonica and facilitate interpretation of results of environmental DNA (eDNA) analysis in their spawning area, we examined the eDNA concentration released by each life history stage of artificially reared Japanese eels in the laboratory using quantitative real-time PCR (qPCR). We also compared eDNA concentrations between before and after artificially induced spawning activities. eDNA was not detected from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
108
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(119 citation statements)
references
References 46 publications
11
108
0
Order By: Relevance
“…While we demonstrate that incorporating allometric scaling coefficients 509 substantially improves models predicting abundance and eDNA concentration at the population 510 level, we have not directly quantified how eDNA production scales allometrically in brook trout 511 at the level of individual organisms. Nevertheless, recent experiments demonstrate that mass-512 specific eDNA production rates tend to decline as individual mass increases (Maruyama et al, 513 2014;Mizumoto et al, 2017;Takeuchi et al, 2019). We found that a scaling coefficient of 0.72 514 best described patterns of eDNA concentration for our study species across our nine study lakes; 515 this value closely aligned with the metabolic scaling coefficient for brook trout from (Hartman & 516 Cox, 2008).…”
Section: Discussion 442supporting
confidence: 76%
See 3 more Smart Citations
“…While we demonstrate that incorporating allometric scaling coefficients 509 substantially improves models predicting abundance and eDNA concentration at the population 510 level, we have not directly quantified how eDNA production scales allometrically in brook trout 511 at the level of individual organisms. Nevertheless, recent experiments demonstrate that mass-512 specific eDNA production rates tend to decline as individual mass increases (Maruyama et al, 513 2014;Mizumoto et al, 2017;Takeuchi et al, 2019). We found that a scaling coefficient of 0.72 514 best described patterns of eDNA concentration for our study species across our nine study lakes; 515 this value closely aligned with the metabolic scaling coefficient for brook trout from (Hartman & 516 Cox, 2008).…”
Section: Discussion 442supporting
confidence: 76%
“…If size classes exhibit different behaviour at high densities, this could further affect estimates of 551 allometric scaling. Future studies examining allometric scaling in eDNA production should 552 therefore incorporate individuals from a gradient of age/size classes and quantify organismal 553 eDNA production at the individual-level, as in (Takeuchi et al, 2019). Notably, the two studies 554 to examine eDNA production rates at an individual level across age/size classes found that 555 larger, older individuals exhibited lower mass-specific eDNA production rates ( Our results provide evidence supporting the hypothesis that eDNA production scales 568 allometrically with organism mass and can be modelled according to the power function: 569…”
Section: Discussion 442mentioning
confidence: 99%
See 2 more Smart Citations
“…Under natural conditions, differences in fish physiology, diet and behavior are likely to affect this process and confound the interpretation of eDNA-based results from a water body (Klymus et al, 2015). For perch and eel, Maruyama et al (2014) and Takeuchi et al (2019), respectively, found lower eDNA shedding rates for adults in comparison to juveniles, which is likely caused by the ontogenetic decrease in metabolic rates (Winberg, 1960). However, these findings could not be confirmed in an experiment with a salmonid species (Mizumoto et al, 2018).…”
Section: Introductionmentioning
confidence: 99%